Issuance of Special Investigation Orders in Split Cases by the Prosecutor’s Office under Law Number 8 of 1981 on Criminal Procedure - Arief Koswara; Ahmad Jamaludin (PDIH Untag Semarang, 2025)
The issuance of a Special Investigation Order by prosecutors to separate cases raises issues because the mechanism is not expressly regulated in the Criminal Procedure Code. This study aims to analyze the issuance of a Special Investigation Order in case separation by prosecutors and examine its compliance with the provisions of criminal procedure law as stipulated in Law Number 8 of 1981 concerning the Criminal Procedure Code. Separation, namely the separation of a criminal case into several case files to expedite the legal process, is often applied in complex special crimes such as corruption. This study uses a normative legal method with a statutory and conceptual approach, analyzing relevant laws and regulations, scientific literature, and official documents. The results of the study indicate that although separation has gained internal legitimacy through Attorney General Instruction Number 8 of 2023, it still requires clear regulations in the Criminal Procedure Code to ensure legal certainty and prevent abuse of prosecutorial authority. The normative implication of these findings is the urgent need for clear legal regulations to govern the practice of case separation, in order to align with the principle of legality and ensure legal certainty.